Paradigma “Smile Design” dalam Rehabilitasi Estetik pada Gigi Anterior Rahang Atas - Anna Muryani; 0pik Taopik Hidayat (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
The development of aesthetic rehabilitation techniques or smile design in the field of dentistry has brought a paradigm shift in the field of restoration and aesthetic. Dentists in planning treatment for patients should do a proper analysis on the patient, not just think about the treatment of one tooth, but the whole tooth being the problem in patient’s smile. This case aims to report the paradigm of “smile design” in the aesthetic rehabilitation on maxillary anterior teeth. The 23-year-old male patient came to the dental clinic with complaints of caries on the upper anterior teeth with wide damage. Pulp vitality tests showed positive results on teeth 13, 12 and negative on teeth 14,21,22,24. Radiographic examination revealed radiolucent image until dentin in teeth 12 and 13, as well as radiolucent image until pulp and widening of periodontal membrane on teeth 14,21,22,24. Case management in these patients is smile design analysis on maxillary anterior teeth. Direct composite veneer restoration is performed on teeth 13, 12, while root canal treatment is done on teeth 14, 21, 22 and 24 followed by fiber reinforced composite and all porcelain crowns. Patients is consulted to periodontic department for gingival aesthetic correction treatment with crown lengthening and gingival depigmentation. Aesthetic rehabilitation techniques or smile design involves evaluation of certain elements which is face analysis, jaw-facial relationship analysis, dental relation to the center line of the face, tooth on lips analysis, dental relation to the gingiva, and teeth shape and color analysis.These elements are all interconnected with each other.